2022
DOI: 10.3390/jcdd9080274
|View full text |Cite
|
Sign up to set email alerts
|

Carvedilol versus Metoprolol in Patients with Ventricular Tachyarrhythmias

Abstract: The study investigates the prognostic role of treatment with carvedilol as compared to metoprolol in patients with ventricular tachyarrhythmias. A large retrospective registry was used including consecutive patients on beta-blocker (BB) treatment with episodes of ventricular tachycardia (VT) or fibrillation (VF) from 2002 to 2015. Patients treated with carvedilol were compared to patients with metoprolol. The primary prognostic outcome was all-cause mortality at three years. Secondary endpoints comprised a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…One of the third generations that are applicable in the markets with several concentrations is carvedilol (CAR) found in the market as monotherapy or in combination with other classes to control HBP, it is lipophilic, act on ß1-and ß2 receptors(non-selective blockers) also has additional advantages of block norepinephrine binding to α1 -adrenergic receptors, so control blood pressure by its mechanism 8 , it reduce tachycardia through inhibition of beta-adrenoreceptors, has an action on α1 -adrenergic receptors relaxes the smooth muscles in the vasculature, leading to reduced peripheral vascular resistance and an overall reduction in blood pressure 19 , 20 , indicated for the chronic therapy of heart failure with reduced ejection fraction (HFREF), reduction arterial BP, left ventricular dysfunction myocardial infarction (MI) in the clinically stable patient. On the other hand, CAR is completely absorbed from GIT.…”
Section: Introductionmentioning
confidence: 99%
“…One of the third generations that are applicable in the markets with several concentrations is carvedilol (CAR) found in the market as monotherapy or in combination with other classes to control HBP, it is lipophilic, act on ß1-and ß2 receptors(non-selective blockers) also has additional advantages of block norepinephrine binding to α1 -adrenergic receptors, so control blood pressure by its mechanism 8 , it reduce tachycardia through inhibition of beta-adrenoreceptors, has an action on α1 -adrenergic receptors relaxes the smooth muscles in the vasculature, leading to reduced peripheral vascular resistance and an overall reduction in blood pressure 19 , 20 , indicated for the chronic therapy of heart failure with reduced ejection fraction (HFREF), reduction arterial BP, left ventricular dysfunction myocardial infarction (MI) in the clinically stable patient. On the other hand, CAR is completely absorbed from GIT.…”
Section: Introductionmentioning
confidence: 99%
“…In another study conducted among patients with the same chronic disease (ESRD), Wu et al revealed that bisoprolol was significantly associated with lower rates of all-cause mortality than carvedilol [5]. Among patients with ventricular tachyarrhythmia, Schupp et al found that the all-cause mortality rate was not significantly lower in metoprolol users compared to carvedilol [6]. With no significant difference, all-cause mortality rate among patients with advanced stages of heart failure was higher among nebivolol users than bisoprolol [7].…”
Section: Introductionmentioning
confidence: 99%